Pengaruh Citra Merek dan Persepsi Harga terhadap Keputusan Pembelian Smartphone Samsung - Djaya, Hendrawan Tanu; Sitinjak, Tony (Global Research on Economy, Business, Communication, and Information, 2025)
Smartphone have become a primary necessity for many people. Samsung, as a market leader, faces the challenge of maintaining brand image and influencing price perception to affect consumer purchasing decisions. This research analyse the influence of brand image and price perception on Samsung smartphone purchase decisions. This research employs a quantitative method with a non-probability sampling technique using judgmental sampling. Data was collected through an online questionnaire administered to 95 Samsung smartphone users. The collected data was then analysed using SPSS versions 25. The results of the study show that brand image has a positive and significant influence on Samsung smartphone purchase decisions. Price perception also has a positive and significant influence on Samsung smartphone purchase decisions. Based on the result, Samsung is recommenced to implement continuous innovation to improve product quality and remain competitive with other brands. For future research, researchers can consider incorporating additional variables such as promotions or other relevant factors to obtain more optimal results.